Hg Formation and Transformation Characteristics in Flue Gas of Coal-fired Boiler - Xiaoxue AN; Sheng SU; Jun XIANG; Jianxun HUANG; Jizhuang XU; Lele WANG; Yi WANG; Song HU; Zijun YIN; Zhonghui WANG (发电技术)
The transfer characteristics and removal capability of Hg in ultra-low emission facilities such as selective catalytic reduction (SCR), low temperature electrostatic precipitator, seawater desulfurization and wet electrostatic precipitator in a 300 MW coal-fired boiler of a power plant were studied under different working conditions and different types of coal. The results show that under different working conditions, the total emission concentration of mercury is basically 1.16-2.90 μg/m3. The final release of mercury into the atmosphere is mainly composed of elemental mercury and a small amount of oxidized mercury, the particulate mercury was completely removed. Most mercury is removed in seawater flue gas desulfurization. The overall removal efficiency of mercury of low temperature electric precipitator, a seawater flue gas desulfurization scrubber and wet electric precipitator is 25%, 62% and 37% respectively on average. The proportion of Hg2+ is the key to affect the efficiency of mercury removal in flue gas, and the higher proportion of Hg2+ in flue gas is beneficial to obtain higher efficiency in electrostatic precipitators and seawater flue gas desulfurization devices. In the 300 MW coal-fired boiler of a power plant equipped with a selective catalytic reduction unit, a low temperature electrostatic precipitator, a seawater flue gas desulfurization scrubber, and a wet electrostatic precipitator and other ultra-low emission facilities, the average removal rate of total mercury is about 83%, which can achieve greater levels of mercury removal.